Neuro-Ophthalmic Complications in Patients Treated With CTLA-4 and PD-1/PD-L1 Checkpoint Blockade. Issue 4 (December 2021) - Sun, Michel M.; Seleme, Nicolas; Chen, John J.; Zekeridou, Anastasia; Sechi, Elia; Walsh, Ryan D.; Beebe, Johanna D.; Sabbagh, Osama; Mejico, Luis J.; Gratton, Sean; Skidd, Philip M.; Bellows, David A.; et al.
Abstract : Background: In recent years, CTLA-4 and PD-1/PD-L1 checkpoint inhibitors have proven to be effective and have become increasingly popular treatment options for metastatic melanoma and other cancers. These agents work by enhancing autologous antitumor immune responses. Immune-related ophthalmologic complications have been reported in association with checkpoint inhibitor use but remain incompletely characterized. This study seeks to investigate and further characterize the neuro-ophthalmic and ocular complications of immune checkpoint blockade treatment. Methods: A survey was distributed through the secure electronic data collection tool REDCap to neuro-ophthalmology specialists in the North American Neuro-Ophthalmology Society listserv. The study received human subjects approval through the University of California at Los Angeles Institutional Review Board. The survey identified patients sent for neuro-ophthalmic consultation while receiving one or more of a PD-1 inhibitor (pembrolizumab, nivolumab, or cemiplimab); PD-L1 inhibitor (atezolizumab, avelumab, or durvalumab); or the CTLA-4 inhibitor ipilimumab. Thirty-one patients from 14 institutions were identified. Patient demographics, neuro-ophthalmic diagnosis, diagnostic testing, severity, treatment, clinical response, checkpoint inhibitor drug used, and cancer diagnosis was obtained. Results: The checkpoint inhibitors used in these patients included pembrolizumab (12/31), nivolumab (6/31), combined ipilimumab with nivolumab (7/31, one of whom also received pembrolizumab during their course of treatment), durvalumab (3/31), ipilimumab (2/31), and cemiplimab (1/31). Malignant melanoma (16/31) or nonsmall cell lung carcinoma (6/31) were the most common malignancies. The median time between first drug administration and the time of ophthalmological symptom onset was 14.5 weeks. Eleven patients had involvement of the optic nerve, 7 patients had inflammatory orbital or extraocular muscle involvement, 6 patients had ocular involvement from neuromuscular junction dysfunction, 4 patients had cranial nerve palsy, and 4 patients had non neuro-ophthalmic complications. Use of systemic corticosteroids with or without stopping the checkpoint inhibitor resulted in improvement of most patients with optic neuropathy, and variable improvement for the other ophthalmic conditions. Conclusion: This study describes the variable neuro-ophthalmic adverse events associated with use of immune checkpoint inhibitors and contributes a more thorough understanding of their clinical presentations and treatment outcomes. We expect this will increase awareness of these drug complications and guide specialists in the care of these patients. Abstract : Supplemental Digital Content is Available in the Text.